Minimum tillage and vegetative barrier effects on crop yields in relation to soil water content in the Central Kenya highlands - Guto, Samuel; Ridder, N.A. de; Giller, Kenneth E.; Pypers, Pieter; Vanlauwe, Bernard (Elsevier, 2012)
The sub-humid zone of Central Kenya is water deficient due to regular intra-seasonal dry spells that constrain rain-fed crop production. A study was initiated to investigate the effects of minimum tillage and vegetative barriers on soil and water conservation and crop yield. There were two tillage practices; minimum and regular tillage and two vegetative barriers; leucaena consisting of leguminous trees (Leucaena trichandra), and Napier consisting of Napier grass (Pennisetum purpureum) in addition to a control without barriers. Maize and soybean crops were planted in rotation in the terraces between the barriers. Soil moisture content was measured near the barriers and at the centre of the terraces. Vegetative barriers impeded run-off and controlled soil loss. There was a positive linear relationship between soil loss and rainfall for Napier grass barriers. For leucaena barriers, soil loss increased quadratically with rainfall. At the onset of rainfall, soil water content increased for all tillage and barrier practices. With more rainfall, soil water content increased marginally without barriers while with barriers there was continued soil water build-up. At the end of the wet period and across tillage practice, the soil contained 43% more water near leucaena barriers compared with no barriers and 20% more at the centre of the terrace. For Napier barriers, the soil water content was 60% more near barriers and 30% more at the centre of the terrace. Without barriers, the soil water content was 10% more with regular rather than minimum tillage. At the cessation of rainfall, soil water declined in all tillage and barrier treatments. At the centre of the terraces and across barriers, soil water reduction compared with no barriers was 10% less for minimum tillage and 24% more for regular tillage. Nearer barriers, the soil water reduction (relative to regular tillage without barriers) for leucaena barriers was 56% less with minimum tillage and 77% less with regular tillage. Conversely with Napier barriers, there was stronger water reduction with minimum (116%) than regular tillage (102%). At the centre of the terraces and across vegetative barriers, the upper soil layers (<60 cm) retained more water compared with deeper layers for minimum than regular tillage over the dry period. Near barriers but between tillage and barriers treatments, leucaena barriers extracted more water from deeper soil layers (>60 cm) independent of tillage practice. In contrast, Napier barriers extracted more water from the upper end of the profile, especially with minimum tillage. Napier barriers with minimum tillage suppressed maize row-grain yields (relative to regular tillage without barriers) by 26% over a distance of 3 m along the barrier crop interface. Maize yield suppression for Napier barriers with regular tillage was less pronounced (occurring over a distance of 1.5 m) and improved maize crop performance at the centre of the terraces increased overall row grain yields by 14% relative to regular tillage without barriers. Soybean yields with Napier barriers were suppressed over a distance of 0.5 m in the barrier crop interface. Maize and soybean yield suppression with leucaena barriers for the different tillage practices was less pronounced, and improved crop performance at the centre of terraces consistently compensated for any yield reductions at the barrier crop interface. Between tillage and barriers treatments, the degree of yield suppression was related to the water use pattern of the vegetative barriers, and more severe with Napier than with leucaena barriers, particularly with minimum tillage. A possible strategy for successful introduction of a combination of minimum tillage and the vegetative barriers into water deficient highland regions would include leucaena barriers with minimum tillage due to less competition for water between barriers and companion crops. Napier barriers with minimum tillage do not combine well due to strong competition for available water between the barriers and crops, even when intensely harvested.